A novel classifier combining G protein-coupled receptors and the tumor microenvironment is associated with survival status in glioblastoma - Guo, Chunyu; Yu, Cong; Gao, Weizhen; Ren, Dabin; Zhang, Yisong; Zheng, Ping (Frontiers in Pharmacology, 2023)
Background: Numerous studies have highlighted the crucial role of G protein-coupled receptors (GPCRs) in tumor microenvironment (TME) remodeling and their correlation with tumor progression. However, the association between GPCRs and the TME in glioblastoma (GBM) remains largely unexplored.Methods: In this study, we investigated the expression profile of GPCRs in GBM using integrated data from single-cell RNA sequencing and bulk sequencing. Surgical samples obtained from meningioma and GBM patients underwent single-cell RNA sequencing to examine GPCR levels and cell-cell interactions. Tumor microenvironment (TME) score is calculated by the infiltrated immune cells with CIBERSORT.Results: Our findings revealed a predominantly increased expression of GPCRs in GBM, and demonstrated that the classification of GPCRs and TME is an independent risk factor in GBM. Patients with high GPCR expression in the tumor tissue and low TME score exhibited the worst outcomes, suggesting a potentially aggressive tumor phenotype. On the other hand, patients with low GPCR expression in the tumor tissue and high TME score showed significantly better outcomes, indicating a potentially more favorable tumor microenvironment. Furthermore, the study found that T cells with high GPCR levels displayed extensive cell-cell connections with other tumor and immune cells in the single cell RNA analysis, indicating their potential involvement in immune escape.In conclusion, GPCRs in combination with TME classification can serve as prognostic markers for GBM.GPCRs play an essential role in tumor progression and the TME in GBM.